2005
DOI: 10.1161/01.str.0000155686.73908.3e
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Nimodipine in Subcortical Vascular Dementia

Abstract: Background and Purpose-Evidence of drug efficacy in vascular dementia (VaD) is scanty. Therapeutic trials should address VaD subtypes. We studied the efficacy and safety of the calcium antagonist nimodipine in subcortical VaD. Methods-242 patients defined as affected by subcortical VaD based on clinical (ICD-10) and computed tomography criteria were randomized to oral nimodipine 90 mg/d or placebo. Results-230 patients (121 nimodipine, mean age 75.2Ϯ6.1; 109 placebo, 75.4Ϯ6.0) were valid for the intention-to-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 23 publications
1
54
0
1
Order By: Relevance
“…Both groups were allowed to continue with unspecified antihypertensive treatment as prescribed before the beginning of the study except alpha methyldopa. The results showed that the control group had significantly more adverse (cerebrovascular) events than the treatment group [11][12] . For cardiovascular events the trend was similar but reached significance in only one of the studies 12 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Both groups were allowed to continue with unspecified antihypertensive treatment as prescribed before the beginning of the study except alpha methyldopa. The results showed that the control group had significantly more adverse (cerebrovascular) events than the treatment group [11][12] . For cardiovascular events the trend was similar but reached significance in only one of the studies 12 .…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that the control group had significantly more adverse (cerebrovascular) events than the treatment group [11][12] . For cardiovascular events the trend was similar but reached significance in only one of the studies 12 . In a subgroup analysis of participants with sub-cortical vascular dementia 13 , no significant differences in these adverse events were found, although again the same trend was observed (fewer events in the treatment group).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A Cochrane 2002 review analyzed three studies using nimodipine (90 mg/day) between 12 and 24 weeks in patients with vascular dementia, and a benefit was found in some cognition and global assessment scales [226] A multicenter, double-blind, randomized study comparing nimodipine (90 mg/day) to placebo for the treatment of subcortical vascular dementia for 52 weeks was published, without finding a benefit in the cognition scales [227].…”
Section: Nimodipinementioning
confidence: 99%
“…27) Only nimodipine has been established as a neuroprotectant after subarachnoid hemorrhage. 22) In addition, L-type calcium channel blockers have potential therapeutic uses for subcortical vascular dementia 19) and Parkinson's disease. 23) Thus, as a L-type calcium channel antagonist, sarpogrelate may represent a new and important therapeutic agent in the treatment of cerebral ischemia, subarachnoid hemorrhage, dementia, and Parkinson's disease.…”
mentioning
confidence: 99%